PENGARUH KONTROL DIRI TERHADAP PERILAKU AGRESI VERBAL SISWA SMP NEGERI 22 KOTA JAMBI - Febriani, Widia; Rahman, K. A.; Sarman, Freddi (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2025)
Self-control can direct a person to behave in a positive directionand in accordance with the norms that apply in society. Students who have good self-control will suppress the tendency to carry out negative behavior such as verbal aggression. This verbal aggressive behavior causes problems that can lead to fights and disharmonious relationship between students. This research aims to determine the effect of self-control on students’ verbal aggressive behavior. This research is a quantitative research using ex-post facto method with 50 students as research samples obtained through purposive sampling techniques. Analysis of research data using simple regression analysis techniques via SPSS IBM 25. The research results found that there was an influence of self-control on students’ verbal aggressive behavior at SMP Negeri 22 Kota Jambi. This result obtained from the Fcount value of 140.995 with Sig. 0.006 < 0.05. The value of R Square is 0.148, meaning that self-control has an influence of 14.8% on the verbal aggressive behavior of students at SMP Negeri 22 Kota Jambi.